Successful treatment of a chronic oroantral fistula infected with extensively drug resistant bacteria using long‐term oesophageal tube feeding and several non‐conventional treatments in a horse. Issue 3 (2nd December 2021) - Fletcher, JR; Yuen, KY; Stewart, AJ; Young, AC; Gibson, JS; James, OA; Medina‐Torres, CE; Forde, BM; Sole‐Guitart, A
Abstract : Background: Chronic oroantral fistulae (OAF) with secondary sinusitis can occur following repulsion of cheek teeth in horses. Case Report: An 8‐year‐old Andalusian cross gelding presented with an iatrogenic clinical crown fracture of tooth 209, which underwent repulsion of its apical portion (day 0). The horse was treated with intramuscular penicillin and intravenous gentamicin (5 days), followed by oral trimethoprim‐sulphonamide (10 days) and then oral doxycycline (14 days). The acute iatrogenic OAF created during the initial repulsion persisted; a chronic OAF was identified on day 24. On day 48, septic sinusitis with multidrug‐resistant (MDR) Escherichia coli was confirmed. Although susceptible to enrofloxacin in vitro, 30 days of therapy was unsuccessful. Subsequent serial cultures grew multiple MDR and extensively drug‐resistant (XDR) gram‐negative microorganisms. Whole‐genome sequencing (WGS) revealed multiple sequence types of E. coli, with a range of resistance and virulence genes. The orientation of the OAF, regional osteomyelitis and septic sinusitis were confirmed with computed tomography on day 70. On day 74, enteral nutrition was provided through a cervical oesophagostomy tube for 3 months for prevention of oral feed contamination. The OAF was treated with various alternative therapeutics, including apple cider vinegar, propolis and amikacin impregnated products, until resolution on day 116. Conclusion: These non‐conventional therapeutics, antimicrobials and long‐term oesophagostomy contributed to the successful treatment of a complicated OAF. In the future, WGS may be useful to inform antimicrobial selection when MDR or XDR organisms are identified.